FAKTOR YANG MEMENGARUHI MINAT GENERASI MUDA DALAM MELANJUTKAN USAHATANI KELUARGA DI KECAMATAN AKABILURU KABUPATEN LIMA PULUH KOTA - Irawan, Ferdi Mahkota; Alfikri; Afrizal, Roni (Green Engineering Society, 2023)
The agricultural sector is one of Indonesia's third largest economic sources after the industrial and trading sectors. In 2022, it is recorded that 34.6% of the workforce will be absorbed by the agricultural sector. agricultural labor is still dominated by mature and old age workers. This is due to the lack of desire of the younger generation to continue farming family. The research objective is to analyze the factors that influence the interest of the younger generation in continuing family farming. The research was carried out in Akabiluru District, Lima Puluh Kota District with sampling using the roscoe theory formula in the Koto Tangah Nagari, Batu Ampa and Batuhampar. data analysis used binary logistic regression with independent variables including gender, motivation, age, land area, education, agricultural image, and community environment. The results showed that the variable age and land area had a positive effect, while the motivational variable had a negative effect.